2015
DOI: 10.5501/wjv.v4.i2.124
|View full text |Cite
|
Sign up to set email alerts
|

Key role of human leukocyte antigen in modulating human immunodeficiency virus progression: An overview of the possible applications

Abstract: Host and viral factors deeply influence the human immunodeficiency virus (HIV) disease progression. Among them human leukocyte antigen (HLA) locus plays a key role at different levels. In fact, genes of the HLA locus have shown the peculiar capability to modulate both innate and adaptive immune responses. In particular, HLA class I molecules are recognized by CD8(+) T-cells and natural killers (NK) cells towards the interaction with T cell receptor (TCR) and Killer Immunoglobulin Receptor (KIR) 3DL1 respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…On the other hand, the HLA system plays an important role in the outcome and severity of many infectious diseases such as the human immunodeficiency virus [ 9 ] and the malaria parasite [ 10 ]. This role is pronounced in class I molecules that are expressed on all nucleated cells, and play a central role in immune regulation by presenting cytoplasmic peptides and in particular viral antigens.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the HLA system plays an important role in the outcome and severity of many infectious diseases such as the human immunodeficiency virus [ 9 ] and the malaria parasite [ 10 ]. This role is pronounced in class I molecules that are expressed on all nucleated cells, and play a central role in immune regulation by presenting cytoplasmic peptides and in particular viral antigens.…”
Section: Discussionmentioning
confidence: 99%
“…One key mechanism that viruses use to shape host immune recognition and attack is the alteration of HLA antigen expression on infected cells (54, 55). Fortunately, a large body of studies have revealed that particular KIR and HLA molecule interactions are significant in viral infection protection and control (56, 57).…”
Section: Function Of Human Leukocyte Antigen-f and Kir3ds1 Interactiomentioning
confidence: 99%
“…Human leukocyte antigen (HLA) plays an essential role in immune regulation. The polymorphisms of HLA are significantly related to the susceptibility and severity of many diseases, such as tumors (Sadagopan et al 2022 ), autoimmune diseases (Naito and Okada 2022 ), immunodeficiency diseases (Grifoni et al 2015 ), allergic diseases (Daya et al 2021 ), infectious diseases (Medhasi and Chantratita 2022 ), metabolic diseases (Tekola Ayele et al 2012 ), and so on. Each person has multiple alleles that make up the individual HLA type.…”
Section: Introductionmentioning
confidence: 99%